Comparative gastrointestinal adverse effects of GLP-1 receptor agonists and multi-target analogs in type 2 diabetes: a Bayesian network meta-analysis - Xie, Xingmiao; Yang, Shuiyuan; Deng, Shuzhen; Liu, Yuying; Xu, Zhibin; He, Binghong (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to evaluate and compare the gastrointestinal adverse effects associated with different GLP-1 receptor agonists (GLP-1RAs) and multi-target analogs in patients with type 2 diabetes mellitus (T2DM) using a Bayesian network meta-analysis.MethodsA systematic search of PubMed, Embase, Cochrane Library, and ClinicalTrials.gov was conducted to identify randomized controlled trials (RCTs) assessing the gastrointestinal adverse events of GLP-1RAs in T2DM patients. Inclusion criteria included adult patients with confirmed T2DM receiving any GLP-1RA, with the outcomes focused on gastrointestinal adverse events such as nausea, vomiting, diarrhea, constipation, dyspepsia, and reduced appetite. Bayesian network meta-analysis was used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) for the comparison of gastrointestinal side effects among different GLP-1RAs.ResultsA total of 48 RCTs involving 27,729 participants were included in the analysis. The overall incidence of gastrointestinal adverse events was 11.66%, with nausea being the most frequent (21.49%) and reduced appetite the least frequent (5.49%). Tirzepatide had the highest risk of inducing nausea and diarrhea, while dulaglutide and lixisenatide had the lowest risks. Exenatide exhibited the highest incidence of vomiting, while dulaglutide showed a lower risk. Semaglutide demonstrated a significantly higher risk of diarrhea compared to other GLP-1RAs.ConclusionThis study highlights significant differences in the gastrointestinal adverse event profiles of various GLP-1RAs. Tirzepatide exhibited the highest risk of gastrointestinal side effects, whereas dulaglutide and exenatide showed relatively better tolerability. These findings provide valuable insights for clinicians to make informed treatment decisions, emphasizing the importance of individualized therapy based on patient tolerance.Systematic Review RegistrationCRD42024592308.